Proceedings of the 5th International Conference on Community Development (AMCA 2018) 2018
DOI: 10.2991/amca-18.2018.65
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Logarithm: What are the Difficulties That Students Have?

Abstract: This study aims at determining students' difficulties in understanding logarithm material. The subject of this study are 10th grade students. The type of research is qualitative descriptive, and it applied several steps in the form of providing test to the students, determining the difficulties and interviewing students who had difficulty on the material. The result of the study showed that there were several difficulties such as applying definition, determining logarithmic properties to solve problems, applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…While the literature provides a broad overview of the difficulties students confront in solving logarithmic problems and relates them to mistakes in manipulating logarithmic expressions and to challenges in understanding the meaning of the logarithmic concept (Dintarini, 2018), the current study's findings show that incorrect notions of logarithm, due to poor prior understanding and knowledge, also contribute to such errors. Aziz et al (2017) aver that students make common mistakes due to misconceptions about logarithm, arithmetical problems, and misuse of algebra concepts.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…While the literature provides a broad overview of the difficulties students confront in solving logarithmic problems and relates them to mistakes in manipulating logarithmic expressions and to challenges in understanding the meaning of the logarithmic concept (Dintarini, 2018), the current study's findings show that incorrect notions of logarithm, due to poor prior understanding and knowledge, also contribute to such errors. Aziz et al (2017) aver that students make common mistakes due to misconceptions about logarithm, arithmetical problems, and misuse of algebra concepts.…”
Section: Discussionmentioning
confidence: 65%
“…Logarithm has a reputation for being difficult (Dintarini, 2018). This is probably because of its presentation as the inverse of exponential functions (Weber, 2016).…”
Section: Perceptions and Troubling Reputation Of Logarithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Quasi tutti gli elaborati prodotti dagli studenti hanno mostrato difficoltà di vario tipo nella gestione del concetto di logaritmo. L'analisi condotta nel presente articolo non intendeva focalizzare questi aspetti a proposito dei quali si rinvia a Dintarini (2018). Alcuni degli errori presenti negli elaborati riguardanti l'interpretazione del documento sono di natura linguistica, come ad esempio in Gaia: «Per trovare il logaritmo in base n di un numero y vuol dire trovare quel numero x che elevato alla base n mi dia y» per intendere che la base n va elevata all'esponente x.…”
Section: Ddmunclassified
“…Since the indirect definition is still valid in algebra textbooks despite the many problems reported in the educational literature, it may be a major cause of student difficulties. (Dintarini, 2018) found that some students did not fully understand the meaning of logarithms. In the end, students had difficulty applying the definition of logarithms to problems.…”
Section: Introductionmentioning
confidence: 99%